Respostas
respondido por:
28
-10x + 10y = 30
x + 2y = 3 (*10)
_________________
-10x + 10y = 30
10x + 20y = 30
_________________
30y = 60
y = 60/30
y = 2
-10x + 10y = 30
-10x + 10(2) = 30
-10x + 20 = 30
-10x = 30 - 20
-10x = 10
x = -10/10
x = -1
Tirando a prova temos:
-10x + 10y = 30
-10(-1) + 10(2) = 30
10 + 20 = 30
30 = 30
x + 2y = 3
-1 + 2(2) = 3
-1 + 4 = 3
3 = 3
x + 2y = 3 (*10)
_________________
-10x + 10y = 30
10x + 20y = 30
_________________
30y = 60
y = 60/30
y = 2
-10x + 10y = 30
-10x + 10(2) = 30
-10x + 20 = 30
-10x = 30 - 20
-10x = 10
x = -10/10
x = -1
Tirando a prova temos:
-10x + 10y = 30
-10(-1) + 10(2) = 30
10 + 20 = 30
30 = 30
x + 2y = 3
-1 + 2(2) = 3
-1 + 4 = 3
3 = 3
Anônimo:
pra vc aprender
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás